The Effectiveness of Extracurricular Management in Developing Student Interests and Talents at MAN Kota Batu - Muamalatul Hikmah; Ahmad Ta'rifin; Silna Farodis; Amalia Shinta Defi; Abiyyu Al Fatih; Ahmad Ziyan Hanif (Social Journal of Studies in Education, 2025)
This study aims to determine the effectiveness of extracurricular management in developing students' interests and talents at MAN Kota Batu. The research employed a descriptive qualitative approach through observation, interviews, and documentation. The results indicate that effective extracurricular management is supported by strong leadership, adequate facilities, and active participation of all stakeholders. Main challenges include resource limitations, time management issues among students, and less optimal parental support. Findings demonstrate that the success of fostering student potential relies heavily on systematic management and a conducive environment. Therefore, extracurricular management requires continuous evaluation and strong collaboration to optimize activities in character building, interests, and talents comprehensively. This research provides valuable contributions as an evaluation basis and development of extracurricular management models in schools.